2023
DOI: 10.1590/1414-431x2023e12279
|View full text |Cite
|
Sign up to set email alerts
|

Gelsolin inhibits autophagy by regulating actin depolymerization in pancreatic ductal epithelial cells in acute pancreatitis

Abstract: Gelsolin (GSN) can sever actin filaments associated with autophagy. This study investigated how GSN-regulated actin filaments control autophagy in pancreatic ductal epithelial cells (PDECs) in acute pancreatitis (AP). AP was produced in a rat model and PDECs using caerulein (CAE). Rat pancreatic duct tissue and HPDE6-C7 cells were extracted at 6, 12, 24, and 48 h after CAE treatment. HPDE6-C7 cells in the presence of CAE were treated with cytochalasin B (CB) or silenced for GSN for 24 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Caerulein (CAE), an analog of cholecystokinin, has been widely used in vitro and in vivo to establish models of AP (22). Our previous studies found that the change in protein expression of autophagy marker, the apoptosis and pyroptosis protein expression of NLPR3, cleaved caspase-1 and cleaved caspase-3, the tight junction protein expression of ZO-1 and occludin in HPDE6-C7 cells treated with CAE in vitro were consistent with the rat model of AP (8,9,23,24). In the present study, it was hypothesized that MCU-associated mitochondrial Ca 2+ overload promotes mitophagy by regulating the PINK1/Parkin pathway in AP.…”
Section: Mitochondrial Calcium Uniporter Promotes Mitophagy By Regula...mentioning
confidence: 67%
See 2 more Smart Citations
“…Caerulein (CAE), an analog of cholecystokinin, has been widely used in vitro and in vivo to establish models of AP (22). Our previous studies found that the change in protein expression of autophagy marker, the apoptosis and pyroptosis protein expression of NLPR3, cleaved caspase-1 and cleaved caspase-3, the tight junction protein expression of ZO-1 and occludin in HPDE6-C7 cells treated with CAE in vitro were consistent with the rat model of AP (8,9,23,24). In the present study, it was hypothesized that MCU-associated mitochondrial Ca 2+ overload promotes mitophagy by regulating the PINK1/Parkin pathway in AP.…”
Section: Mitochondrial Calcium Uniporter Promotes Mitophagy By Regula...mentioning
confidence: 67%
“…A reduction in the expression of TOMM20, which is a translocase of the outer mitochondrial membrane 20, indicates that impaired mitochondria may be removed by mitophagy. Our previous study found that CAE induced autophagy activation in the early stage of AP ( 8 ). RR mainly inhibits mitochondrial Ca 2+ and is recognized as a potent inhibitor of MCU.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation